SISTEM RANGKA PEMIKUL MOMEN KHUSUS (SRPMK) DALAM PERENCANAAN STRUKTUR BETON BERTULANG TAHAN GEMPA - Liliana Liliana; Frieda Frieda; Annisa Tri Hapsari (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
With the history of earthquakes that occurred in Central Borneo Province, it is very necessary to plan earthquake resistant building structures, especially in the implementation of reinforced concrete building structures. Earthquake-resistant reinforced concrete structure planning is carried out using a Special Moment Resisting Frame System with the object of research being the Integrated Lecture Building of the University of Palangka Raya. In planning earthquake-resistant reinforced concrete structures, the requirements described in SNI 2847-2019 are required. The results of the planning of structural components for the structure of the Palangka Raya University Integrated Lecture Building, namely the structural components under review, used 30/60 beam dimensions and 60/60 column dimensions. In the 30/60 beam design, the left bearing reinforcement is 6D25 tension-8D29 pressed, the field reinforcement is 4D25 tension-2D29 pressed, the right support reinforcement is 5D25 tension-4D29+4D25 pressed, and the left/right joint shear reinforcement 2 legs ∅12–120 mm for the plastic hinge area and 2 legs ∅12–150 mm for the area outside the plastic hinge. On the planning of the 60/60 column obtained longitudinal reinforcement 24D25 and reinforcement in the plastic hinge 4 legs ∅12–100 mm, outside the plastic hinge 4 legs ∅10–150 mm, and in the lap joints 4 legs ∅12–100 mm. On examination the requirements for strong column-weak beam based on SNI 2847-2019 have been fulfilled. So that the planning of the Special Moment Resisting Frame System in increasing the resistance of the building to the possibility of large earthquake forces is appropriate and safe.